WATER-model: An optimal allocation of water resources in Turkey, Syria and Iraq - Pao-Yu Oei; Markus Siehlow (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Political instability of several countries in the Middle East is overshadowing one of the biggest challenges of the upcoming century: Water - a natural resource that is easily taken for granted, but whose scarcity might lead to serious conflicts. This paper investigates an optimal Water Allocation of the Tigris and Euphrates Rivershed by introducing the WATER-Model. A series of scenarios are analyzed to examine the effects of different levels of cooperation for an optimal water allocation. Special emphasize is put on the effects of filling new Turkish reservoirs which can cause additional welfare losses if these actions are not done on a basin-wide coordinated basis. Modeling results show that Turkey is most efficient in its water usage. However, using the water for irrigation purposes in Turkey, instead of the Iraqi or Syrian domestic and industrial sector, decreases the overall welfare. Especially the Euphrates basin might thus encounter losses of up to 33% due to such strategic behaviour. The predicted water demand growth in the region is going to increase this water scarcity further. Minimum flow treaties between riparian countries, however, can help to increase the overall welfare and should therefore be fostered.
Keywords: C61; Q25; O53; D74; 330; Integrated Water Resources Management; Euphrates Tigris rivershed; non linear modeling; transboundary water resources allocation